Willingness to Pay of Urban Households for the Conservation of Natural Resources and Cultural Heritage in a Neighboring Rural Area A CVM Study. - Pacatan-Tan, Rosalina
Koronadal households benefit from Lake Sebu?s natural resources (lakes, waterfalls, rivers and springs, forest land, agricultural land) and cultural heritage (arts and handicrafts such as T?nalak weaving, brass casting, beadwork, and wood carving; music and dances; festivals; and beliefs and traditions of the T?boli indigenous tribe) in terms of recreation, good image and sense of pride, tourism income generation, the supply of high-quality tilapia, agricultural products supply, potential hydroelectric power source, biodiversity, and climate change mitigation. These benefits are integrated into a single estimate using the contingent valuation method. In the study, a sample of 524 Koronadal households was asked for their willingness to pay (WTP) or contribute to natural resources and cultural heritage conservation efforts in Lake Sebu in the form of a lump-sum monthly amount collected together with their electricity bill payment. The mean WTP per month is estimated to be Php 52.42 (USD 1.04) using the probit regression estimates (parametric mean) and Php 64.39 (USD 1.27) using the Turnbull formula (non-parametric mean), both less than 1% (0.26?0.33%) of average monthly household income. Multiplying the annualized WTP by the number of households in Koronadal, total potential annual contributions from Koronadal City would range from Php 29.2?35.7M, about 3% of the City Government?s 2019 total revenues of Php 932.6M (Koronadal City Government Budget Office). Even just a fraction of this potential collection can support essential conservation efforts in Lake Sebu, which ? up to the present ? have been inadequate due to financial constraints. Moreover, the results of the regression analysis reveal that households are more likely to support the conservation program if the amount of required contribution is smaller and household income is higher. Older and more educated respondents are, likewise, more likely to support the program.